Simultaneous Cervical and Lumbar Spinal Degenerative Stenosis: Diagnostic and Treatment Challenge - Wendlassida Joelle Stéphanie TIENDREBEOGO/ZABSONRE; Denlewende Sylvain ZABSONRE; Abdoulaye SANOU; Amitandi Armand 1er Jumeau OGOABIGA; Yakouba HARO; Inoussa ZOUNGRANA; Fulgence KABORE; Dieu-Donné OUEDRAOGO (Indonesian Journal of Rheumatology, 2023)
Background: In simultaneous cervical and lumbar degenerative stenosis (tandem spinal stenosis), the cervical clinical signs may mask the lumbar ones. Treatment is initially conservative in non-plegic cases. In the event of surgery, there is no consensus regarding the segment to be approached first. The purpose of this work was to describe our management of this condition. Methods: This was a 6-year retrospective study in the rheumatology and neurosurgery departments. All usable medical records of cases of simultaneous degenerative stenosis of the cervical and lumbar spine were included. Results: We retained 84 squares. The average age was 57.1 years; the sex ratio 0.9. All the patients presented cervical and lumbar clinical signs. They had started at the lumbar spine in 46 cases (54.8%) and cervical in 38 cases (45.2%). A full spinal MRI had been performed in 50%. Conservative treatment was effective in 36 patients (42.9%). Of the 32 patients (66.7%) operated, 16 had been operated both the cervical and lumbar spine (7 simultaneous surgeries including percutaneous discolysis in one of the segments in 4 cases). The cervical spine had been operated on first in 7 of the 9 cases of staggered surgery. After an average follow-up of one month, the evolution was favorable in 47 cases (56%); stationary 21 (25%). Conclusion: Conservative treatment was effective in about half of the cases. Full spine MRI and staggered surgery were the most commonly performed. However, simultaneous surgery prioritizing the least aggressive gestures seems better.